2016
DOI: 10.3109/09273948.2015.1099680
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in Uveitic Macular Edema Refractory to Previous Immunomodulatory Treatment

Abstract: Treatment with tocilizumab can be considered in chronic uveitic macular edema even if previous immunomodulatory therapy has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…[9][10][11] Additionally, TCZ in adults with non-anterior uveitis and refractory uveitis-related cystoid macula edema is well established. [14][15][16][17][18][19][20][21] The STOP-Uveitis Study demonstrated that monthly intravenous TCZ infusions significantly improved the visual, anatomic and inflammatory outcomes in patients with non-anterior uveitis with limited systemic and ocular adverse effects. 14 Comparable results were seen with sarilumab subcutaneous, another anti-IL-6 receptor, in adult uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Additionally, TCZ in adults with non-anterior uveitis and refractory uveitis-related cystoid macula edema is well established. [14][15][16][17][18][19][20][21] The STOP-Uveitis Study demonstrated that monthly intravenous TCZ infusions significantly improved the visual, anatomic and inflammatory outcomes in patients with non-anterior uveitis with limited systemic and ocular adverse effects. 14 Comparable results were seen with sarilumab subcutaneous, another anti-IL-6 receptor, in adult uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Small retrospective studies demonstrated the efficacy of tocilizumab in the treatment of refractory uveitic macular edema. [44][45][46] As an alternative for IL-6, T h 17 polarization might be driven through an IL-1b/IL-1R signaling pathway downstream of Mincle/ caspase activation and recruitment domain 9 (CARD 9)dependent signaling and inflammasome activation. The latter pathway is activated by, for example, mycobacterial peptidoglycan 47 and also plays a central role in autoimmune diseases of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…; Deuter et al. ; Goldhardt & Rosen ). As long‐standing CME will result in irreversible damage to as a result of outer retinal and photoreceptor damage, anatomical resolution of the CME will not lead to improvement in BCVA (Androudi et al.…”
Section: Discussionmentioning
confidence: 99%
“…In Androudi et al (2010), intravitreal adalimumab showed no efficacy in improving BCVA or decreasing CMT; however, it should be noted that in this particular study, all patients had refractory CME at baseline. Uveitic CME is thought to result from increased vascular permeability due to the breakdown of BRB and is a major risk factor for vision loss (Fardeau et al 2015;Goldhardt & Rosen 2016) and often difficult to manage (Androudi et al 2010;Fardeau et al 2015;Deuter et al 2016;Goldhardt & Rosen 2016). As longstanding CME will result in irreversible damage to as a result of outer retinal and photoreceptor damage, anatomical resolution of the CME will not lead to improvement in BCVA (Androudi et al 2010).…”
Section: Summary Of Evidencementioning
confidence: 99%